Synthesis and Characterization and Binding of Amine-Palladium(II) Complexes and Their Interaction with DNA - Huq, Fazlul; Tayyem, Hasan; Abdullah, Ahmed; Beale, Philip; Fisher, Keith (Asian Journal of Chemistry, 2010)
Three new planaraminepalladium(II) complexes of the form trans-PdCl2L2, code named TH5, TH6 and TH7, where L=3-hydroxypyridine, 2-hydroxypyridine and 4-hydroxypyridine, respectively have been synthesized and characterized by elemental analyses and IR, mass and sup 1H NMR spectral studies. The nature of interaction of the compounds with salmon sperm DNA and pBR322 plasmid DNA has also been investigated. The compounds differ in their molar conductivity values, ability to cause DNA damage and changes in DNA conformation. Solution of TH7 in 1 : 1 mixture of DMF and water has the highest molar conductivity value whereas that of TH5 has the lowest value indicating that the compounds differ in degree of dissociation into ions. TH5 is found to cause the greatest damage to pBR322 plasmid DNA and is also most effective in preventing BamH1 digestion. Both the DNA damage and prevention of BamH1 digestion are believed to be a consequence of binding of the compounds with DNA. The results illustrate structure-activity relationship.